1994
DOI: 10.1038/eye.1994.158
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of strabismus surgery in childhood exotropia

Abstract: SUMMARYThe results of squint surgery in 42 children with primary, non-paralytic, childhood exotropia are analysed. A 'favourable outcome', defined as a final alignment for near and distance within ±10 dioptres of straight, or within ±20 dioptres of straight with evidence of bi nocular single vision, was achieved in 39 (93%) children.The factors affecting the final outcome are discussed, including age of onset, age at the time of surgery, pre operative and post-operative amblyopia, refractive error, anisometrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
6

Year Published

1997
1997
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 12 publications
1
22
0
6
Order By: Relevance
“…The optimum age for surgery is when the child is able to undergo orthoptic assessment or when the functional and cosmetic symptoms become evident. 12,13 In our study, there was a female preponderance similar to that observed in study by Cass and Gregerson.…”
Section: Discussionsupporting
confidence: 77%
“…The optimum age for surgery is when the child is able to undergo orthoptic assessment or when the functional and cosmetic symptoms become evident. 12,13 In our study, there was a female preponderance similar to that observed in study by Cass and Gregerson.…”
Section: Discussionsupporting
confidence: 77%
“…The favourable age for operation is when the child can be assessed for orthoptic correction and also when the functional and cosmetic symptoms become too apparent. [15][16][17][18] According to the study conducted by Junejo SA et al, 19 the desired postop effect was seen with preoperative deviation of < 60 PD. With deviation > 60 PD, there was difficulty in aligning the eyes with operation only on one eye.…”
Section: Discussionmentioning
confidence: 99%
“…Para este estudo, foi adotado o critério de sucesso cirúrgico como ortotropia ± 10 Δ , assim como a maioria dos autores (1,(11)(12)(13)(14) . O sucesso desses procedimentos depende de avaliação pré-operatória completa, considerando-se os possíveis fatores desestabilizadores (15) .…”
Section: Comentáriosunclassified
“…Outros autores também identificaram idade como fator relacionado ao sucesso cirúrgico, relatando melhores resultados nos pacientes operados antes dos seis anos de idade (1) . Entretanto, na maioria dos trabalhos encontrados, a variável mais relacionada ao sucesso cirúrgico foi uma supercorreção inicial (7)(8)(9)13,17) . Como apresentado na tabela 3, os desvios pós-operatórios dos dois grupos mostraram-se semelhantes (desvio pós-operatório imediato: p=0,228, final: p=0,143), com valores discretamente superiores, tanto para as médias quanto para os desvio-padrões, para o grupo A, mas ainda assim dentro do que consideramos sucesso cirúrgico.…”
Section: Comentáriosunclassified